A case study on Erdheim ‐ Chester Disease - Erdheim, Jakob; Koeck, Harald (Archives of Case Reports, 2020)
In this brief essay, Harald Koeck offers an introduction to Professor Jakob Erdheim, an eminent pathologist of Vienna. Koeck is an independent researcher at different Pathology Departments (Department of Pathology St. Poelten with Prof. Hans Bank MD, Department of Pathology MSMC N.Y. with Prof. Alan L. Schiller MD, Department of Pathology Minsik with Prof. Jurij Bandaschewski MD and since 2008 at the Jakob Erdheim Institute Vienna Hospital Hiezing, Chair Univ. Prof. Walter Ulrich MD.